TWO-DIMENSIONAL VELOCITY STRUCTURE BENEATH NORTHERN EURASIA DERIVED FROM THE SUPER LONG-RANGE SEISMIC PROFILE QUARTZ - Ryberg T.; Mechie J.; Wenzel F.; Fuchs K.; Egorkin A.; Solodilov L. (My University, 1996)
A two-dimensional velocity structure for the mantle down to a depth of 700 km derived from super long-range nuclear explosion seismic data recorded along the Quartz profile in northern Eurasia is presented. The profile extends from the Russian Platform, across Western Siberia to the Altai mountains. A detailed structural image of the lithosphere and asthenosphere shows strong lateral variations along the profile. The subcrustal lithosphere to a depth of 100 km is characterized by lateral variations of the P-wave velocity between 7.7 and 8.7 km/sec. The seismic data are consistent with the Ural mountains having a crustal root. Another important finding in the data is an additional discontinuity in the mantle transition zone at 530 km. This discontinuity could represent one or more phase transitions known to occur at about this depth. At present, the nuclear-seismic records are believed to represent a key data set to prove the existence of this much debated upper mantle discontinuity.